Monitoring additive manufacturing based products in clinical trials. (26th September 2017) - Marinakis, Yorgos D; Harms, Rainer; Walsh, Steven T
Abstract: Under U.S. federal regulation 31 CFR §312, medical interventions must report on a series of clinical trials phases before being submitted for approval for release to the U.S. market. Clinical trials are now being performed on medical interventions that were constructed through additive manufacturing. Serious adverse events (SAEs) in clinical trials would be the first indicator of problems in the application of additive manufacturing to medical interventions. Techniques for the visual display of aggregates of reports from clinical trials involving additive manufacturing will become more important as data becomes Big Data. Novel methods are needed for economically displaying clinical trials Big Data to industry watchers, investors and other interested parties. Aggregate indicators of additive manufacturing-based clinical trials SAEs would be of particular interest to industry watchers, investors and policy makers. In the present study, indexes are constructed comprising percents of interventional clinical trials reporting SAEs from 1997–2014, aggregated by the year in which the study commenced. The present research falls within the discipline of biomedical informatics.